2022
DOI: 10.3390/medicina58020176
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between MALAT1 Polymorphism rs3200401 C > T and the Risk of Overall Cancer: A Meta-Analysis

Abstract: Background and Objectives: At present, the association between the long non-coding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) polymorphism rs3200401 C > T and cancer risk remain controversial. The aim of this meta-analysis was to assess the association between rs3200401 C > T and cancer susceptibility. Materials and Methods: The databases of PubMed, EMBASE and Web of Science were searched for literature published in English until 1 September 2021. The odd ratios (ORs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Wang et al showed that T allele of rs3200401 was protective factor in survival outcomes of patients with advanced lung adenoma 9 . In a recent meta-analysis that did not include lung cancer, the researchers did not find a relationship between the MALAT1 rs3200401 polymorphism and overall cancer risk, rs3200401 C > T polymorphism plays different roles in cancers 52 . Our study revealed that rs3200401 reduces the risk of non-small cell lung cancer and lung squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al showed that T allele of rs3200401 was protective factor in survival outcomes of patients with advanced lung adenoma 9 . In a recent meta-analysis that did not include lung cancer, the researchers did not find a relationship between the MALAT1 rs3200401 polymorphism and overall cancer risk, rs3200401 C > T polymorphism plays different roles in cancers 52 . Our study revealed that rs3200401 reduces the risk of non-small cell lung cancer and lung squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, a recent metaanalysis conducted by Li et al found no significant association between the MALAT1 rs3200401C/T variant and the overall cancer risk. However, it may be linked to a higher risk of colorectal cancer, which needs more studies for further validation [73]. Other MALAT1 functional variants have shown associations with the risk of cancer, for example, colorectal cancer (rs619586, rs664589, and rs1194338) and hepatocellular cancer (rs619586), as confirmed by the recent meta-analysis conducted by Cao et al [74].…”
Section: Discussionmentioning
confidence: 81%
“…Genetic polymorphisms in lncRNAs may influence their expression and function, and thus increase or decrease an individual's susceptibility to the disease, to the extent that the lncRNAs are the direct causative contributors rather than mere genetic markers; this feature would help to assess disease risk and clinical prognosis [21,22]. The SNPs rs3200401 in MALAT1 and rs217727 in H19 are associated with increased risk of T2D [23,24] and different types of cancers [25,26]. Several studies have suggested that there is association between the SNPs rs3200401 and rs217727, and the etiological mechanisms of obesity, such as insulin dysregulation, and abnormal lipid and glucose metabolism [13,20,24].…”
Section: Introductionmentioning
confidence: 99%